Chemical Analysis of NOx Removal Under Different Reduced Electric Fields. (July 2015) - Haddouche, A.; Lemerini, M.
Abstract: This work presents a chemical kinetic analysis of different species involved in nitrogen-oxygen mixed gas induced by stationary corona discharge at room temperature and atmospheric pressure. This study takes into account twenty different chemical species participating in one hundred and seventy selected chemical reactions. The reaction rate coefficients are taken from the literature, and the density is analyzed by the continuity equation without the diffusion term. A large number of investigations considered the removal of NO x showing the effects of N, O and O3 radicals. The aim of the present simulation is to complete these studies by analysing various plasma species under different reduced electric fields in the range of 100-200 Td (1 Td=10 −21 V·m 2 ). In particular, we analyze the time evolution of depopulation (10 −9 –10 −3 s) of NO x . We have found that the depopulation rate of NO and NO2 is substantially affected by the rise of reduced electric field as it grows from 100 Td to 200 Td. This allows us to ascertain the important role played by the reduced electric field.